Pelaksanaan Audit Mutu Pelayanan Keperawatan di RS A Jakarta Barat - Ayu, Vergeina; Handiyani, Hanny; Yatnikasari, Aat (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Implementation of quality improvement in hospitals is still unsatisfactory. One of the causes of this problemis the inadequate implementation of nursing audits by the nursing committee. This study aims to identify theimplementation of the nursing profession audit at Hospital A, West Jakarta. The method used is a pilot studyin the nursing room with the involvement of manager nurses and clinical nurses as many as 140 nurses. Theanalysis from the assessment stage, interviews, observation, distributing questionnaires and focus groupdiscussions, and fishbone analysis found that the nursing profession audit was the task of the nursingsubcommittee that was being improved. The implementation carried out is the latest creation, the auditorteam, audit tools and the implementation of nursing audits. Result: The audit was carried out by determiningthe topic of handover between shifts. The not yet optimal implementation of handover between shifts is theresult of the nursing audit. The conclusion has been that the preparation of a new audit of nursing qualityhas been carried out in RS A, the formation of an auditor team and the compilation of tools in implementingnursing audits. The nursing profession quality audit has been carried out on the topic of handover betweenshifts and the result is that the handover between shifts is optimized. Recommendations for the latest nursingaudits validation, conducting nursing audits on topics according to the needs of the nursing committee andperiodic re-audits.